The Impact of Innovative Accounting Practices on Corporate Governance and Their Reflection on The Credibility of Financial Reports: An Analytical Study - Faraj Gheni Abbood; Baydaa Fadhil Jasim (Journal of Economics, Assets, and Evaluation, 2026)
The research  aims to study the impact of creative accounting practices on corporate governance, specifically (board division based on loans, transparency and disclosure, and capital adequacy), and their effect on the credibility of financial reports at a sample of Iraqi banks listed on the Iraq Stock Exchange for the period (2015-2022). To address this problem and achieve the research objective, the descriptive approach was adopted in analysing the research results, in addition to using the statistical package (SPSS) to analyse the data extracted from the Iraq Stock Exchange. Accordingly, the research produced several findings, the most important of which is the existence of a significant relationship and influence between Innovative Accounting Practices, Corporate Governance, and the Credibility of Financial Reports, which has directly and indirectly contributed to drawing the attention of commercial banks to improve their financial performance. This is because the profits reported by the Iraqi private commercial banks in the research sample do not exhibit a high level of earnings quality due to their reliance on Innovative Accounting Practices in making and giving financial reports, finished deliberate intervention in accounting measurement and disclosure, within or beyond usually putative accounting values, to affect the reported profits. Therefore, the research recommended that the banks in the sample should cease applying Innovative Accounting Practices, as these practices have negative effects on the bank's value and future, necessitating the application of Corporate Governance principles to address these practices and improve the Credibility of Financial Reports.